An Analysis of Judicial Reasoning as a Form of Breaking and Legal Discovery for Ecological Justice - Muhammad Rizky Aditiya; Ikomatussuniah; Ahmad Rayhan (Siyasah Dusturiyah: State Law Review, 2026)
Post-Job Creation Law, environmental approvals are trapped in rigid administrative formalism, ignoring geological vulnerability. This article aims to examine judicial reasoning in Decision No. 59/G/LH/2023/PTUN.JKT as rule-breaking and rechtsvinding for ecological justice. This empirical legal research employs statutory, conceptual, and sociological approaches, utilizing data derived from qualitative interviews and literature reviews. The findings demonstrate that judges performed rule-breaking by deliberately bypassing formal administrative compliance to prioritize public safety. Furthermore, rechtsvinding was successfully implemented through the dominus litis principle when comprehensively examining complex scientific evidence. Ultimately, this corrective ruling perfectly actualizes the Progressive Legal Theory and the Legal Development Theory, asserting unequivocally that corporate investment execution must strictly submit to the absolute ecological threshold boundaries. Therefore, administrative procedures cannot justify ecologically destructive actions; substantive environmental protection must remain the paramount judicial objective to guarantee intergenerational sustainability across modern Indonesia.